ANALISIS PERBANDINGAN PERFORMA PADA PERANCANGAN JARINGAN 5G NEW RADIO MENGGUNAKAN FREKUENSI 3,5 DAN 24 GHz DI KOTA YOGYAKARTA - Dianthy Marya (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2022)
Indonesia is starting to prepare to launch a 5G NR network in the near future to support the implementation of industry 4.0 and the ever-increasing data rate needs. This study will serve as a starting point for planning the deployment of 5G NR technology and as a guide for decision-makers in the Indonesian telecommunications industry. It compares the performance of 5G NR networks based on regional coverage at the 3.5 GHz and 24 GHz frequencies in the City of Yogyakarta. The link budget approach is calculated using the Urban Micro (UMi) and Urban Macro (UMa) propagation models. The calculation results show that the pathloss, cell radius, and number of gNodeB values ??for the 3.5 GHz frequency are 5 sites, while the maximum 24 GHz frequency is 157 sites. The parameter values for coverage, quality, service area, and capacity are then obtained by simulation using the Atoll software. According to the simulation results, the expected PUSCH & PUCCH signal levels and SS-RSRP coverage level achieve satisfactory results with values that are not significantly different in both uplink and downlink circumstances. The quality downlink level prediction simulation in the PDSCH C/(I+N) is rated as very excellent, whereas the quality downlink level prediction is rated as good. While the uplink uses 16 QAM for modulation, the downlink uses 64 QAM for the service area prediction simulation. According to the simulation, the predicted downlink capacity is 180 Mbps, while the predicted uplink speed is 117 Mbps.